A Study to Evaluate the Association of Stress Level and Academic Performance among Nursing Students at College of Nursing (Female) Badin - Khatti, Fatima; Lodhi, Atteqa; Raza, Saad; Ali, Roshan; Din, Fazal; Lal, Jatendar (Indus Journal of Bioscience Research, 2025)
Introduction: Various factors affect academic performance, and stress is one of them. Stress can be defined as any psychological disturbance that impairs one’s ability to work effectively. Stress can affect students' potential to work effectively. This study was conducted to understand the specific effects of stress on nursing students' academic outcomes. Objectives: To evaluate the association and relationship between perceived stress level and academic performance among nursing students at the College of Nursing Female Badin Pakistan. Methods: A cross-sectional study was conducted at the College of Nursing Female Badin. The study evaluated the association between perceived stress levels and academic performance by using a convenience sampling technique. Data were collected on the multi-sectioned questionnaire, Perceived Stress Level Scale (PSS), and Academic Performance Scale (APS). Data were analyzed by using SPSS version 22. The chi-square test and correlation were applied to estimate the association and relationship between stress and academic performance. Results: A total of 99 participants were included in this study. Among the respondents 100% were females. The findings of this current study show that 77.78% of participants experience moderate stress levels, 15.15% of participants experience low stress levels and only 7% of participants experience high perceived stress levels. The positive relationship between stress level and academic performance was estimated at a p-value of 0.002 and r value of 0.275 at a significance level of 0.01. Conclusion: The study conducted at the College of Nursing Female Badin Pakistan revealed a significant association between stress level and academic performance. The positive relationship between stress and academic performance was estimated in this current study, which indicates that students consider stress as positive to enhance their academic performance.